IoT-based infusion monitoring system with blood detection and automatic flow rate control - Pradana Ihsan, Zaky; Sardi, Juli (Journal of Industrial Automation and Electrical Engineering, 2025)
The advancement of technology has driven innovation in health monitoring systems based on Internet of Things(IoT), offering convenience and efficiency in patient condition monitoring. This study develops an IoT based system for monitoring the volume of Nacl (saline) infusion and detecting blood reflux in the infusion tubing to enchance patient care effectiveness. The system utilizes a Wemos D1 Mini microcontroler connected to the blynk application, enabling medical personnel to monitor and control the infusion process in real-time via smartphone. The system is equipped with a Load Cell sensor to measure infusion volume, an LDR sensor to detect blood reflux based on changes in light intensity, and a photodiode sensor to calculate infusion drip rate. Additionally, a servo motor is used to relugate the infusion flow rate by adjusting the pressure on the tubing. All collected data is transmitted in real-time to the IoT platform, allowing healthcare workers to perform continuous monitoring without repetitive manual checks. Testing result show that the system accurately monitors infusion volume, detects blood reflux, and controls drip rate. the implemetation of this device improves monitoring efficiency, accelerates response to changes in patient condition and reduces the potential for human error, The success of this system contributes to the advancement of healthcare technology, particularly in hospital patient monitoring and intensive care settings.